TUMOR-ASSOCIATED LOCALIZED SCLERODERMA IN CONJUNCTION WITH ACQIRED DISSIMINATED FORM OF VITILIGO: A CLINICAL CASE - A. S. Dvornikov; P. A. Skripkina; S. K. Dvornikov; A. P. Raksha; O. V. Minkina (SINAPS LLC, 2017)
We are presenting the clinical and laboratory case of management of 62 years old patient with combined dermatological tumor-associated diseases: localized form of scleroderma, acquired disseminated form of hypopigmentation (vitiligo). The patient initial visit in a medical dermatological facility was due to the emergence of a consistent following complaints such as the sudden appearance of alterated skin sites in the left breast and some later the occurrence of rushes on the skin on the chest area and on the anterior surface of the abdomen. Upon further examination of the patient have been verified malignant tumor of the left breast, therefore appropriate (complex) treatment have been conducted in a medical institution of oncology service. After 1.5 years after the sectoral mastectomy the patient appealed to the dermatologist again with a complaints to the renewed activity of scleroderma process on the skin of the left breast. On the background of activation of dermatological symptoms the patient have been diagnosed recurrent tumor in the left breast. This clinical case is a multipurpose: first of all, it is demonstrates the importance of the principle of oncological vigilance in multidisciplinary daily medical practice which would improve early diagnosis and, consequently, treatment of the underlying disease; secondly, the present clinical case suggests an unexpected paraneoplastic contour of the diseases which are unpopular in this category previously, but generally frequent in the population.